Ethical Screening and Financial Performance: Evidence from US Mutual Funds. - PRATVIEL, Héloïse (2016)
This paper investigates the performance of US SRI Funds, over the time period January 2011 to April 2016. The paper focuses on heterogeneity of screening methodologies by using panel data analysis, which extends the research about SRI funds’ performance. Using different measures of performance, the study examines the effect of ethical screening on financial performance and financial risk. I find that screening intensity has a curvilinear effect on financial performance, and on risk as well, what makes the choice of screens really sensitive. Therefore, I also analyse the impact of screening areas and approaches. I find that Governance screening has a positive impact on fund’s performance, whereas restricted screening and avoiding industries badly impact financial performance.